2019
DOI: 10.1515/jmbm-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization and machining performance evaluation of rice husk/epoxy an agricultural waste based composite material

Abstract: Natural fibers from agricultural waste have received more attraction than traditional synthetic fibers in recent years. In present investigation epoxy/rice husk composite has been fabricated to utilize the agricultural waste which can be recycled easily and overcome the pollution problems due to smoke and fine silica ash. Study of interfacial bonding and dispersion of rice husk in epoxy resin has been studied through scanning electron microscope image. Characterization of fabricated composites has been done by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…RH/ epoxy for mechanical properties characterization and performance of machining was studied using three different epoxy/ RH composites were used as husk's particulate form, hybrid (mixing particulate with equal proportion with full RH), and RH used [41]. Results showed that particulate RH reinforced composites have higher ultimate tensile strength.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…RH/ epoxy for mechanical properties characterization and performance of machining was studied using three different epoxy/ RH composites were used as husk's particulate form, hybrid (mixing particulate with equal proportion with full RH), and RH used [41]. Results showed that particulate RH reinforced composites have higher ultimate tensile strength.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…[13] Agricultural residues are an appealing source of nanocellulose which is an abundant, ecological, and economical replacement of other limited natural as well as synthetic fibers. [14][15][16] Prominent agricultural crop sugarcane (Saccharum) has a yield of about 1.8 billion tons per year containing 40-50 wt% cellulose in bagasse which is noticeably much more than various crop residues mainly wheat straw (33 wt%), corn cobs (34 wt%), corn stalks (35 wt%), and rice straw (36 wt%). [17][18][19] Sugarcane bagasse (SCB) is a low-cost, plentiful, and biodegradable residue that makes it encouraging nanoreinforcement in novel green composites.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibres such as cotton [13], rice husk [14,15], kenaf [16], water hyacinth [17], flax [18], jute [18], ginger [19,20] and sugar palm [21] from plants have attracted the attention of many researchers in the past, and they are used because of their important properties such as low cost of materials, ease of availability and biodegradability [22]. For example, cotton fibres were used by Boufi et al [13] with plasmonic nanoparticles for the destruction of harmful molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk fibres were also used in the development of aluminium-based green metal composites to reduce soil pollution [14]. Jain et al [15] used agricultural waste rice husk-reinforced epoxy for coating, electronic implements, aerospace and automotive structures. Besides that, many scientists have made an effort on cellulose fibre as conducting composites (i.e.…”
Section: Introductionmentioning
confidence: 99%